A Comparison Of Modified Atmosphere Packaging Under Ambient Conditions And Low Temperatures Storage On Quality Of Tomato Fruit - Mathooko, Francis M. (Rural Outreach Program, 2003)
Low temperature and modified atmosphere packaging (MAP) were evaluated for their effectiveness in extending the postharvest storage life of tomato (Lycopersicon esculentum Mill.) fruits. Fruits were harvested at the mature-green stage of ripeness, washed, sorted and treated with a solution of sodium hypochlorite (150 ppm chlorine). The fruits were packaged in low density polyethylene bags (0.044 mm) and kept at ambient conditions of 24±2 0C and relative humidity (RH) of 65±2% or held in environmental chambers at 15 0C and RH of 65% for 4 weeks. The fruits were then transferred to ambient conditions of air, temperature and RH for a further one-week to simulate marketing conditions. Samples were evaluated initially and thereafter every week for weight loss, titratable acidity (TA), soluble solids content (SSC), pH, chlorophyll content, ascorbic acid content and visual appearance. MAP reduced weight loss better than low temperature storage. MAP was also superior in delaying ripening in the fruits for the entire four weeks as evidenced by delayed increase in SSC, chlorophyll degradation and increase in ascorbic acid content which are associated with the fruit ripening. After two weeks of storage at 15 0C most of the fruits had started shriveling, thereby leading to loss of brightness in color and there were signs of mold infection. Under MAP the carbon dioxide and ethylene concentrations in the bags increased to 9% and 31 ppm, respectively. Upon transfer of fruits to ambient conditions, fruits held under MAP ripened normally with no signs of carbon dioxide injury. At the end of five weeks, 50% of fruits held at 15 0C were spoilt while only 26% of fruits under MAP were spoilt. These results indicate that under tropical conditions the quality and storage life of tomato fruits can be extended and ripening delayed better by MAP than by low temperature storage owing to fruit susceptibility to chilling injury.
Keywords: Ascorbic acid; Low temperature storage; Lycopersicon esculentum; Modified atmosphere packaging; Tomato